Nec vi nec insidiis, leo et draco: the Lion, the Dragon and the Triumph of Christ - Milinović, Dino (Array, 2009)
The article analyses the symbolic meaning of animals, in particular the lion and the dragon in relation to Christological and imperial symbolics in later Roman empire.